Application of Project-Based Learning (PjBL) Models with STEM Approaches in Dynamic Electricity Material Learning - Agantina Venalia; Tomo Djudin; Erwina Oktavianty (Berkala Ilmiah Pendidikan Fisika, 2022)
This research aims to determine the effect of the Project Based Learning (PjBL) model with the STEM approach to improving learning outcomes in dynamic electricity material in class XII MIPA students of SMAK Abdi Wacana. The research used designed one group pre-experimental pretest-posttest. Design using the measurement of data collection techniques on tests conducted before and after treatment. Analysis of data was undertaken with the normality, homogeneity, Wilcoxon test, and analysis effect size. The results showed that (1) Before and after the Project-Based Learning (PjBL) model with a STEM approach was implemented, learning results for dynamic electricity material were different (P-value 0.05), (2) Application of the PjBL models with STEM approaches in dynamic electrical material learning is effective in improving student cognitive learning outcomes in class XII MIPA SMAK Abdi Wacana. An average pre-test score of 31.22, a post-test score of 61.83, a standard deviation value of 20.22, and an effect size (ES) value of 1.5136 belong to the high category. The results of this study are expected to be considered by teachers in choosing effective learning models and approaches to improve student cognitive learning outcomes.